SAT0062 Test for Serum Progranulin Autoantibodies Can Reduce The Seronegative Status in Rheumatoid Arthritis by One Third. (15th July 2016) - Assmann, G.; Zinke, S.; Gerling, M.; Fadle, N.; Preuss, D.; Pfreundschuh, M.; Thurner, L.
Abstract : Background: Progranulin autoantibodies (PGRNabs) have been previously described in sera of patients with different autoimmune diseases such as ANCA associated vasculitis, large vessel vaskulitis, Crohn's disease, polyarthritis including psoriatic arthritis and rheumatoid arthritis, whereas healthy controls and patients with different non-rheumatological disorders have shown a prevalence less than 1% [Ref.]. At primary diagnosis of rheumatoid arthritis as well as during the course of diseases at least 25% of RA patients have never developed serum RF or ACPA. Here we conducted a study on RA patients who were tested for RF, ACPA, and PRGNabs to evaluate the prevalence of serostatus in RA. Objectives: Prevalence of serum PRGNabs in RA with stratification into seropositive RA patients with the proof of serum RF and/or ACPA and seronegative RA patients. Methods: From Nov 2011 till Dec 2013 sera of 271 RA patients were collected and analyized for RF-IgM, ACPA-IgG, and PGRNabs with ELISA (as previously published) using a retrospective, blinded, non-randomized study design. All patients were on treatment with conventional DMARDS (n=165) or TNF inhibitors (n=106). All patients fullfilled the ACR criteria from 1987 and the revised diagnostic EULAR/ACR criteria from 2011. RA patients characteristics concerning age, gender, treatment history, radiological joint imaging, and duration of disease were availiable. Results: The overall prevalence of PGRNabs in RA patients was 29, 2%. 222 RA patients were seropositive for RF and/or ACPA, 49 RA patients were seronegative. Testing for PRGNabs resulted in significantly higher prevalence of PRGNabs in RF- and ACPA-seronegative RA patients compared to RA patients with seropositivity in at least one of serummarkers RF or ACPA (27.5% versus 36.7%, p=0.021, Chi2 test) [Figure ]. The prevalence of PRGNabs in RF-positive RA patients were significant higher than in ACPA-positive RA (25.0% vs. 29, 6%, p=0.019, chi2 test). The disease duration did not differ between in PRGNabs negative or positive RA patients (8.1 vs. 7.9 years). Conclusions: PGRNabs are positive in more than 30% of sera of RA patients who are seronegative for RF-IgM and ACPA. These results suggest that testing for PRGNabs can reduce the seronegative status in RA patients. However, the data has to be confirmed by a larger validation cohort of RF and ACPA negative RA patients. References: Thurner L, Zaks M, Preuss KD, Fadle N, Regitz E, Ong MF, Pfreundschuh M, Assmann G. Progranulin antibodies entertain a proinflammatory environment in a subgroup of patients with psoriatic arthritis. Arthritis Res Ther. 2013;15(6):R211. Disclosure of Interest: None declared